Defining the Optimization Criteria for the Functioning of Logistics and Distribution Centres - Šafran, Mario; Babić, Darko; Tomašić, Dubravko (Promet - Traffic&Transportation, 2008)
Planning of distribution understands the development of afeasible and viable distribution plan of finished products fromthe producers, via logistics and distribution centres, storage orcrossdocking, to end users. Furthermore, planning represents asupp01t to decision-making by identifying the alternatives of thefuture activities and by selecting the good and optimal ones. It isimportant to note that the scope of planning of logistics and distributionprocesses is not limited only to the planning of production,transport or distribution. It covers the entire logisticsand distribution process with all these elements.